Too early for admission? A Telemedicine follow up comparison of mild COVID-19 patients from the Emergency Department and Clinics - Khalid, Imran; Saeedi, Mohammad; Alzarnougi, Elaf M.; Alraddadi, Abdullah; Afifi, Afnan; Imran, Maryam; Alshukairi, Abeer; Akhtar, Muhammad Ali; Imran, Manahil; Khalid, Tabindeh (International Journal of Health Sciences, 2021)
Objective: Mildly symptomatic COVID-19 patients may seek medical attention either in the Emergency Department (ED) or Ambulatory Clinics (AC). However, it is unclear if ED patients have different characteristics and outcomes than AC patients when discharged under telemedicine surveillance, which we explored in this study. Methods: Patients with mild or asymptomatic COVID-19 disease referred to a multidisciplinary Telemedicine clinical service (TM-CS) program in an urban tertiary-care hospital, between June 2020 and February 2021, were evaluated. Those referred from ED were labeled “ED Group” and ones from AC as “AC Group.” Their characteristics, clinical features and outcomes including telemedicine parameters, subsequent ED visits, hospital admission, oxygen requirements, intensive care unit (ICU) admission, and mortality were compared. Results: Out of 1132 confirmed non-admitted COVID-19 patients, 526 with mild (89%) or asymptomatic (11%) disease were enrolled in TM-CS. Majority of these were referred from ED (n = 370; 70%) and rest (n = 156, 30%) from the AC. Patients in the ED group compared to AC group, had higher BMI (28.9 vs. 27.5), higher Charlson Comorbidity Index (1.4 vs. 0.9), and higher incidence of comorbidities (50% vs. 22%), P ≤ 0.01. However, there were no differences in the ED and AC groups in subsequent ED visits (26% vs. 24%), hospital admission (18% vs. 15%), oxygen requirements (5% vs. 4%), ICU admission (1% vs. 2%), and mortality (0.3% vs. 0.6%), respectively (P > 0.40). Conclusion: Significant number of mild COVID-19 patients head to the ED for initial assistance but have similar outcomes to AC patients. TM-CS could be a safe alternative for follow-up monitoring of these patients.